2022
DOI: 10.1002/smll.202203036
|View full text |Cite
|
Sign up to set email alerts
|

Robust Heterostructures in Two‐Dimensional Perovskites by Threshold‐Dominating Anion Exchange

Abstract: Heterostructures play an irreplaceable role in high‐performance optoelectronic devices. However, the preparation of robust perovskite heterostructures is challenging due to spontaneous interdiffusion of halogen anions. Herein, a vapor‐phase anion exchange method universally suitable for the preparation of robust 2D Ruddlesden–Popper perovskite (RPP) heterostructures is developed. A variety of heterostructures are fabricated based on exfoliated RPP microplates (MPs). Depending on the specific organic cations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The bulky 2T spacer is more efficient in preventing halide ion diffusion in these vertical heterostructures. A similar spacer cation dependence of anion exchange has also been shown in X 2 PbBr 4 /​X 2 PbI 4 heterostructures, with PEA showing a slower diffusion compared to BA …”
Section: Halide Ion Migrationsupporting
confidence: 70%
See 2 more Smart Citations
“…The bulky 2T spacer is more efficient in preventing halide ion diffusion in these vertical heterostructures. A similar spacer cation dependence of anion exchange has also been shown in X 2 PbBr 4 /​X 2 PbI 4 heterostructures, with PEA showing a slower diffusion compared to BA …”
Section: Halide Ion Migrationsupporting
confidence: 70%
“…A similar spacer cation dependence of anion exchange has also been shown in X 2 PbBr 4 /X 2 PbI 4 heterostructures, with PEA showing a slower diffusion compared to BA. 56 Our group compared anion exchange between physically paired 2D perovskite films with bromide and iodide. 48 We found that when a n = 10 bromide perovskite and a n = 10 iodide perovskite with PEA spacers were annealed together (facing each other), halide ion exchange occurred, giving a mixed halide perovskite as shown in Figure 4A.…”
Section: Halide Ion Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-crystalline perovskite nanostructures offer an intrinsic platform for the investigation of ionic movement on a microscopic scale. Research has shown that the reduction of dimensionality may cause significant difference in ionic behavior in one-dimensional (1D) nanowires (NWs) and 2D nanoplates. , In addition, combined with scanning probe measurements, the coupled ionic and optoelectronic transport process can be spatially and temporally resolved, , so that the microscale ionic transport mechanism can be revealed.…”
mentioning
confidence: 99%
“…Research has shown that the reduction of dimensionality may cause significant difference in ionic behavior in one-dimensional (1D) nanowires (NWs) and 2D nanoplates. 32,33 In addition, combined with scanning probe measurements, the coupled ionic and optoelectronic transport process can be spatially and temporally resolved, 34,35 so that the microscale ionic transport mechanism can be revealed. In this work, we investigated the ion-drift-induced giant switchable photovoltaic effect in all-inorganic perovskite NW devices.…”
mentioning
confidence: 99%